Implementasi Game Pembelajaran Interaktif Wordwall - Indarti Rukmana Eko Saputri; Salma Endra Reykha Putri; Rahayu Wulandari; Silvi Fitria Fajriani; Kun Hisnan Hajron (Universitas Islam Sultan Agung, 2023)
This study aims to determine the increase in learning outcomes of Natural Sciences (IPA) elementary school students in the matter of changes in the form of objects through the use of wordwall game media. The research uses a Classroom Action Research (CAR) approach. Data was taken through pretest and posttest provided in the form of interactive games through the wordwall website. The research was conducted on 5th grade students at SD Negeri Danurejo 1 with a total of 20 students. The results of the research from pre-cycle data, the percentage of students who have achieved a completeness score of 15%. In cycle I, the percentage of students who achieved a completeness score increased to 40%. Meanwhile, in cycle II, the percentage of students who achieved a completeness score increased again to 80%. Thus, there was an increase of 23.5% from cycle I to cycle II. So, it can be concluded from this study that the use of wordwall interactive learning games to improve student learning outcomes in high grades can improve Natural Sciences (IPA) learning outcomes in material changes in the shape of objects in high grades.